Empathic concern is part of a more general communal emotion - Zickfeld, J. H. (2017)
Seeing someone in need may evoke a particular kind of closeness that has been conceptualized as sympathy or empathic concern (which is distinct from other empathy constructs). In other contexts, when people suddenly feel close to others, or observe others suddenly feeling closer to each other, this sudden closeness tends to evoke an emotion often labeled in vernacular English as being moved, touched, or heart-warming feelings. Recent theory and empirical work indicates that this is a distinct emotion; the construct is named kama muta. Is empathic concern for people in need simply an expression of the much broader tendency to respond with kama muta to all kinds of situations that afford closeness, such as reunions, kindness, and expressions of love? Across 16 studies sampling 2918 participants, we explored whether empathic concern is associated with kama muta. Meta-analyzing the association between ratings of state being moved and trait empathic concern revealed an effect size of, r(3631) = 0.35 [95% CI: 0.29, 0.41]. In addition, trait empathic concern was also associated with self-reports of the three sensations that have been shown to be reliably indicative of kama muta: weeping, chills, and bodily feelings of warmth. We conclude that empathic concern might actually be a part of the kama muta construct.